Health risk assessment of arsenic in soils from three thermal power plants in Southwest China. Issue 5 (27th May 2020) - Zou, Yiping; Li, Yuhua; Hu, Lei; Yang, Shan; Zhang, Kai; Kang, Jiani; Zhao, Shenwei; Liu, Jialin; Yao, Linying; Jia, Jianli
Abstract: High levels of arsenic (As) contamination in soils from thermal power plants pose a great threat to human health. This study aimed to evaluate the As contamination levels and assess the possible health risk of As in soils from three typical thermal power plants in Southwest China. The concentration of As was detected by using novel collision/reaction cell technology (CCT) with inductively coupled plasma mass spectrometry (ICP-MS, collectively ICP-CCT-MS) after aseptic digestion of soil samples. The carcinogenic risk and hazard quotient were estimated for health risk to workers in the study area by using "Chinese Technical Guidelines for Risk Assessment of Contaminated Sites (HJ 25.3-2014)". Results showed that the concentration of As was between 3.65 and 33.80 mg/kg, and the comprehensive carcinogenic risk level of As was 3–28 times over the maximum acceptable level (10 −6 ), indicating that workers in the study area are facing serious threat of As. Oral ingestion (76.65%) was the main exposure pathway to carcinogenic risk, followed by skin contact (13.15%) and inhalation of soil particles (10.20%). After calculating the safety threshold values under three different exposure pathways (oral ingestion, skin contact and inhalation of soil particles), the minimum safety threshold value (1.59 mg/kg) was selected as the reference safety threshold value of As in the study area. These results provide basic information of health risk assessment of As and environmental management in thermal power plant areas.